Professional Career of Doctors in Tabasco, Mexico: The Case of a Public Higher Education Institution - Silva Payró, Martha Patricia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The career path is the activities that require training and are carried out to obtain theoretical and practical knowledge of a profession. This research aims to describe the variables of the professional trajectory of doctors at a university in Mexico. An instrument (questionnaire) with 12 items was designed and applied. The study had a non-probabilistic sample and was quantitatively descriptive, non-experimental, and cross-sectional, with the participation of 234 doctors. The findings point to the need for diagnostics to identify areas of opportunity concerning research training.